The glucagon receptor antagonist LY2409021 has no effect on postprandial glucose in type 2 diabetes. Issue 2 (6th January 2022) - Hædersdal, Sofie; Lund, Asger; Maagensen, Henrik; Nielsen-Hannerup, Elisabeth; Gasbjerg, Lærke S; Rosenkilde, Mette M; Forman, Julie L; van Hall, Gerrit; Holst, Jens J; Knop, Filip K; Vilsbøll, Tina
Abstract: Objective: Type 2 diabetes (T2D) pathophysiology includes fasting and postprandial hyperglucagonemia, which has been linked to hyperglycemia via increased endogenous glucose production (EGP). We used a glucagon receptor antagonist (LY2409021) and stable isotope tracer infusions to investigate the consequences of hyperglucagonemia in T2D. Design: A double-blinded, randomized, placebo-controlled crossover study was conducted. Methods: Ten patients with T2D and ten matched non-diabetic controls underwent two liquid mixed meal tests preceded by single-dose administration of LY2409021 (100 mg) or placebo. Double-tracer technique was used to quantify EGP. Antagonist selectivity toward related incretin receptors was determined in vitro . Results: Compared to placebo, LY2409021 lowered the fasting plasma glucose (FPG) from 9.1 to 7.1 mmol/L in patients and from 5.6 to 5.0 mmol/L in controls (both P < 0.001) by mechanisms involving reduction of EGP. Postprandial plasma glucose excursions (baseline-subtracted area under the curve) were unaffected by LY2409021 in patients and increased in controls compared to placebo. Glucagon concentrations more than doubled during glucagon receptor antagonism. The antagonist interfered with both glucagon-like peptide 1 and glucose-dependent insulinotropic polypeptide receptors, complicating the interpretation of the postprandial data. Conclusions: LY2409021 lowered FPG concentrations but did not improve postprandial glucose tolerance after a meal in patients with T2D and controls. The metabolic consequences of postprandial hyperglucagonemia are difficult to evaluate using LY2409021 because of its antagonizing effects on the incretin receptors.